2019
DOI: 10.1111/cfs.12691
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment types and adolescent substance use: The role of deviant peer affiliation

Abstract: This is the first study to examine the mediating effects of deviant peer affiliation on the association between different types of child maltreatment and adolescent substance use that includes alcohol, tobacco, and marijuana. Peer deviance is a well‐established correlate of adolescent substance use, but most studies exploring the relationship between child maltreatment and adolescent substance use have failed to include peer deviance. Structural equation modelling was conducted to examine the direct effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Table 3 presents studies examining mediators at the interpersonal level. Four studies identified peer factors as mediating the association between childhood adversity and substance use [49][50][51][52]. One study found socio-emotional difficulties to mediate PLOS ONE…”
Section: Mediation Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 presents studies examining mediators at the interpersonal level. Four studies identified peer factors as mediating the association between childhood adversity and substance use [49][50][51][52]. One study found socio-emotional difficulties to mediate PLOS ONE…”
Section: Mediation Analysesmentioning
confidence: 99%
“…the association between parental separation and alcohol use among adolescent girls, but not boys [52]. Three studies included some aspect of peer substance use or delinquency, which significantly mediated the relationship between adversity and was positively associated with substance use [49][50][51]. Peer deviancy accounted for between 32-63% of the effect of ACEs on substance use [49,50].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Deviant peer affiliation refers to adolescents’ selective affiliation with their peers with serious problem behaviors, including cheating, aggression, and substance abuse [ 27 , 28 ]. There are many causes of deviant peer affiliation in adolescents [ 29 , 30 , 31 ]. One of them might be the poor parent-child relationship.…”
Section: Introductionmentioning
confidence: 99%
“…They have to follow the same rules and behavioral patterns to get accepted by the deviant peers [ 27 , 32 , 33 ]. In return, deviant peer affiliation would undoubtedly cause serious externalization behavior problems, such as drug abuse, aggressive behavior, and bullying [ 29 , 34 , 35 , 36 ]. In other words, parent-child interaction, such as parental behavioral control, is likely to arouse school bullying via deviant peer affiliation.…”
Section: Introductionmentioning
confidence: 99%